2021
DOI: 10.3389/fped.2020.591257
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Primary Ewing Sarcoma of the Penis With Multiple Metastases

Abstract: Background: Ewing sarcoma is the second most common malignant bone tumor in children, but it rarely originates from extra-skeletal sites. The commonly involved sites of soft tissue include paravertebral spaces, lower extremities, the pelvis, head, and neck, while primary extra-skeletal Ewing sarcoma (EES) located in the genitals is extremely rare.Case Presentation: We report a young patient who presented to our hospital with a painful erection of the penis and limited motion of the left hip. Magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Notably, patients with EES tend to have a higher incidence of distant metastasis than skeletal ES patients it has been reported that 30-40% of patients had distant metastasis disease at the time of diagnosis. 10 In our case, the patient did not have metastatic lesions and was treated successfully with chemotherapy, surgery, and radiation therapy. The patient remained free of disease through 2 years of follow-up until now after the completion of treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Notably, patients with EES tend to have a higher incidence of distant metastasis than skeletal ES patients it has been reported that 30-40% of patients had distant metastasis disease at the time of diagnosis. 10 In our case, the patient did not have metastatic lesions and was treated successfully with chemotherapy, surgery, and radiation therapy. The patient remained free of disease through 2 years of follow-up until now after the completion of treatment.…”
Section: Discussionmentioning
confidence: 61%
“…It can be found in unusual locations like the orbit, larynx, scalp, parotid gland, face and neck 16. EES of the penis with multiple metastases, which is extremely rare, has also been reported 17. The usual sites of metastases are the lungs, lymph nodes and bones 9 10.…”
Section: Discussionmentioning
confidence: 99%
“…Another case of penile ES reported by Toh et al occurred in a 21-year-old male with a penile lesion, peritoneal mass, and lung metastasis at the time of diagnosis who was later treated with chemotherapy resulting in initial regression but tumor progression 8 months later [ 13 ]. Additionally, a 17-year-old with ES of the penis presented with metastasis in the lungs, ribs, lumbar vertebrae, and sacrum at the time of diagnosis [ 14 ]. Unfortunately, he died from lung metastasis complications and sepsis 2 months later.…”
Section: Discussionmentioning
confidence: 99%